Transient splenial lesion: Further experience with two cases - Singh, Paramjeet; Gogoi, Dhrubajyoti; Vyas, Sameer; Khandelwal, Niranjan (Indian Journal of Radiology and Imaging, 2010)
Transient splenial lesions (TSL) of the corpus callosum are uncommon radiologic findings that are seen in a number of clinical conditions with varied etiologies. They were first described a decade earlier in patients with epilepsy and hence were thought to be seizure or seizure therapy related. Subsequently, more cases were described by different observers in diseases with different etiologies, and the list is still increasing. Awareness of these lesions is necessary as they are an uncommon finding and have to be differentiated from other infective/noninfective causes. MRI is the imaging modality of choice as these lesions are not seen on routine noncontrast CT scan. The authors here describe two cases which showed TSL, with complete/partial resolution on follow-up scans. The authors also present a review of the literature.
Keywords: MRI; splenium of corpus callosum; transient splenium lesion